CCD (Current Collector Device) Shoes Maintenance Interval Analysis On Jakarta LRT: Analisis Interval Perawatan CCD (Current Collector Device)/Shoe Pada LRT Jakarta - Rachman, Muhammad Aimar; Wibisono, Gendoet Indarto; Dahlan (Jurnal Teknik Transportasi, 2024)
The railway system in Indonesia is currently developing rapidly, as well as railway technology in Indonesia, especially DKI Jakarta, one of which is the Jakarta LRT. CCD (Current Collector Device) which is a device for taking the power supply or distributing electricity from a third rail source. The way the CCD (Current Collector Device) works is that it attaches to the third rail through a shoe that rubs directly against the third rail. Continuous friction causes wear and tear on these components. The current minimum thickness standard for CCD (Current Collector Device) is 20 millimeters. While the thickness of the new condition is 28 millimeters. During the monthly maintenance, it was found that the wear rate was an average of 0.1 millimeters – 0.2 millimeters. This is less significant in carrying out monthly maintenance on the CCD (Current Collector Device). The aim of this research is to analyze the wear rate of the CCD (Current Collector Device) for 1 year and determine the maintenance interval time based on the wear rate.